Comparative analysis of THD for square-wave inverter at different conduction modes - Ranitesh Gupta; Kuldeep Sahay (International Journal of Applied Power Engineering (IJAPE), 2023)
This paper proposes conduction schemes for the most common six-switch voltage sources inverter. Also, a comparative study of the output THD for different conduction modes of switches for a three-phase square wave inverter is done, as the harmonic content of any electrical system is important to analyze its performance. The harmonic distortion of the load voltage and load current is taken as the main constraint to evaluate the performance of the three-phase inverter. So, control strategies for various loads are executed for different modulation schemes of inverter switches using MATLAB/Simulink software. Obtained results show that 150° conduction gives the least THD for output current, and 170° conduction gives the least THD for output voltage for three-phase inverters. Also, harmonic contents are reduced using a passive LC filter at the output of the inverter.